Common Fixed Points in Modular Spaces - Abed, Salwa Salman; Abdul Sada, Karrar Emad (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
In this paper,there are   new considerations about the dual of a modular spaces and weak convergence. Two common fixed point theorems for a -non-expansive mapping defined on a star-shaped weakly compact subset are proved,  Here the conditions of affineness, demi-closedness and Opial's property play an active role in the proving our results.